2003
DOI: 10.1034/j.1600-0560.2003.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Monophasic sarcomatoid carcinoma of the scalp: a case mimicking inflammatory myofibroblastic tumor and a review of cutaneous spindle cell tumors with myofibroblastic differentiation

Abstract: The use of 34betaE12 is essential for the evaluation of myofibroblastic spindle cell tumors with rare cytokeratin reactivity. However, even with immunohistochemical and electron microscopic studies, the diagnosis of spindle cell tumors can be confounded by the multiplicity of nosologic equivalents, such as carcinosarcoma, spindle cell carcinoma, and metaplastic carcinoma. The nomenclature of these spindle cell tumors is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Occasional spindle cell sarcomas, spindle cell melanomas, and sarcomatoid carcinomas contain a marked inflammatory infiltrate, and may show only mild cytological atypia 7779. However, plasma cells are generally not a prominent component of the inflammatory infiltrate in these other tumour types, and most examples show at least focally prominent nuclear hyperchromasia, atypical mitoses, necrosis or vascular invasion, all of which are very unusual in IMT.…”
Section: Diagnostic Approach and Differential Diagnosismentioning
confidence: 99%
“…Occasional spindle cell sarcomas, spindle cell melanomas, and sarcomatoid carcinomas contain a marked inflammatory infiltrate, and may show only mild cytological atypia 7779. However, plasma cells are generally not a prominent component of the inflammatory infiltrate in these other tumour types, and most examples show at least focally prominent nuclear hyperchromasia, atypical mitoses, necrosis or vascular invasion, all of which are very unusual in IMT.…”
Section: Diagnostic Approach and Differential Diagnosismentioning
confidence: 99%
“…34bE12 and CK5/6) have been shown to be the most sensitive. [66][67][68][69] On the basis of the original report, it was thought that spindle cell SCC was most often associated with prior radiation exposure, and that it was an aggressive tumor as half the patients died of disease. 62 However, further studies have shown that while spindle cell SCCs associated with prior radiation behave in a more aggressive manner, those unassociated with radiation are indolent.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…CSs are commonly described in various organs and anatomic sites including urinary bladder, uterus, liver, gastrointestinal tract, lungs, head, and neck [12][13][14]. Relevant clinicopathological and immunohistochemical features are debated in the literature.…”
Section: Discussionmentioning
confidence: 99%